Sugammadex for reversal of neuromuscular blockade: a retrospective analysis of clinical outcomes and cost-effectiveness in a single center - Carron M; Baratto F; Zarantonello F; Ori C (ClinicoEconomics and Outcomes Research, 2016)
Michele Carron, Fabio Baratto, Francesco Zarantonello, Carlo Ori Department of Medicine, Anesthesiology and Intensive Care, University of Padova, Padova, Italy Objective: The aim of the study is to evaluate the clinical and economic impact of introducing a rocuronium–neostigmine–sugammadex strategy into a cisatracurium–neostigmine regimen for neuromuscular block (NMB) management. Methods: We conducted a retrospective analysis of clinical outcomes and cost-effectiveness in five operating rooms at University Hospital of Padova. A clinical outcome evaluation after sugammadex administration as first-choice reversal drug in selected patients (rocuronium–sugammadex) and as rescue therapy after neostigmine reversal (rocuronium–neostigmine–sugammadex) compared to control was performed. A cost-analysis of NMB management accompanying the introduction of a rocuronium–neostigmine–sugammadex strategy into a cisatracurium–neostigmine regimen was carried out. To such purpose, two periods were compared: 2011–2012, without sugammadex available; 2013–2014, with sugammadex available. A subsequent analysis was performed to evaluate if sugammadex replacing neostigmine as first choice reversal drug is cost-effective. Results: The introduction of a rocuronium–neostigmine–sugammadex strategy into a cisatracurium–neostigmine regimen reduced the average cost of NMB management by 36%, from €20.8/case to €13.3/case. Patients receiving sugammadex as a first-choice reversal drug (3%) exhibited significantly better train-of-four ratios at extubation (P<0.001) and were discharged to the surgical ward (P<0.001) more rapidly than controls. The cost-saving of sugammadex as first-choice reversal drug has been estimated to be €2.9/case. Patients receiving sugammadex as rescue therapy after neostigmine reversal (3.2%) showed no difference in time to discharge to the surgical ward (P=0.44) compared to controls. No unplanned intensive care unit (ICU) admissions with rocuronium–neostigmine–sugammadex strategy were observed. The potential economic benefit in avoiding postoperative residual curarization (PORC)-related ICU admission in the 2013–2014 period was estimated at an average value of €13,548 (€9,316–€23,845). Conclusion: Sugammadex eliminated PORC and associated morbidities. In our center, sugammadex reduced the costs of NMB management and promoted rapid turnover of patients in operating rooms, with total cost-effectiveness that counteracts the disadvantages of its high cost. Keywords: neuromuscular blockade; neuromuscular blocking agents; rocuronium; sugammadex; postoperative residual curarization; cost-benefit analysis.